Modeling and simulating cross country banking contagion risks - Stefano Zedda; Antonella Spinace-Casale (Journal of Risk and Financial Management, 2021)
The recent financial crisis proved that financial contagion could spread among countries resulting in disruptive effects. In this paper, by modeling and simulating banking system behavior and linkages across countries, we assess, based on data from the BIS and IMF, the possible outcome of domestic crises and how contagion spreads over countries. Results allow detailing the role of a "lighter" or of a "fueler" of financial crises for each country and assessing how each country can affect each other country by contagion, signaling the importance of financial interdependence between some neighboring countries, and detailing which counterpart country would be affected by the ring-fencing of each considered country's banking system. The method also allows for what-if analyses to optimize the risk exposures, and to plan an emergency strategy in case of alarms coming from specific countries.
Keywords: G01; G17; G15; G21; 330; banking system; international contagion; Monte Carlo simulation; systemic risk